Pengaruh Penanaman Nilai Moderasi Beragama Terhadap Sikap Toleransi Siswa di MA Banu Hasyim Waru Sidoarjo - Afif Usfiyanto; Yuliastutik Yuliastutik (STIKes Ibnu Sina Ajibarang, 2024)
MA Banu Hasyim students have a very high tolerance attitude in every socio-cultural interaction at school. This is based on the instillation of the value of religious moderation which is implemented through the subjects of Citizenship Education and Islamic Religious Education. The aim of this research is to find out how the value of religious moderation is instilled at MA Banu Hasyim Waru Sidoarjo, to find out how students' attitudes of tolerance are at MA Banu Hasyim Waru Sidoarjo, and to find out how the instillation of religious moderation values is on students' tolerance attitudes at MA Banu Hasyim Waru Sidoarjo. By using quantitative research methods with a correlation approach. The sample in this research was all MA Banu Hasyim Waru Sidoarjo students because it was a population study. The variable The data collection technique uses questionnaires and documentation. Based on the data analysis carried out, it is known that the cultivation of religious moderation values at MA Banu Hasyim Waru Sidoarjo is going